Novel Autophagy-Related Gene Signature Investigation for Patients With Oral Squamous Cell Carcinoma - Huang, Lihong; Yu, Xinghao; Jiang, Zhou; Zeng, Ping (Frontiers in Genetics, 2021)
The correlation between autophagy defects and oral squamous cell carcinoma (OSCC) has been previously studied, but only based on a limited number of autophagy-related genes in cell lines or animal models. The aim of the present study was to analyze differentially expressed autophagy-related genes through The Cancer Genome Atlas (TCGA) database to explore enriched pathways and potential biological function. Based on TCGA database, a signature composed of 4 autophagy-related genes was established by multivariate Cox regression models and a Gene Expression Omnibus dataset (GSE85446) was applied for external validation. Furthermore, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed to explore the function of autophagy-related genes and their pathways. The most significant GO and KEGG pathways were enriched in several key pathways that were related to the progression of autophagy and OSCC. Four prognosis-related genes (CDKN2A, NKX2-3, NRG3, and FADD) were identified by univariate Cox regression, and a prognostic risk score was constructed with these 4 genes. Patients were then divided into 2 groups (i.e., high risk and low risk) in terms of the median of risk score. Furthermore, prognosis of these 2 groups and results showed that patients at the low-risk group had a much better prognosis than those at the high-risk group, regardless of whether they were in the training datasets (P<0.001) or validation datasets (P=0.044). Multivariate Cox regression results indicated that the risk score of the 4 autophagy-related gene signatures could greatly predict the prognosis of patients after controlling for several clinical covariates. The findings of the present study revealed that autophagy-related gene signatures play an important role in OSCC and are potential prognostic biomarkers and therapeutic targets.